Zombies and COVID-19: An Examination of the Psychological Contagions Through the Pandemic and Zombie Movies - Jia, Yixuan (Journal of Student Research, 2023)
Two and a half years ago, a new infectious disease later named COVID-19 caused a respiratory illness outbreak in Wuhan, China. By now, much research has been done across various fields on its biological effects on the human body for the sake of controlling the virus, while researchers across the world have conducted limited studies regarding its psychological and socio-political impacts on the population. This research focuses on the effect of three types of contagions, consumer behavior contagion, deliberate self-harm contagion, and hysterical contagion, on people's behavior. By comparing the effects of these contagions in COVID-19 and several zombie movies, this research paper concluded that the spread of fear in both COVID-19 and zombie movies is causing the spread of these contagions.